Method for preparing carbon fiber from acrylonitrile and ice crystal grade acrylic acid

By using ice crystal -grade acrylic acid and acrylonitrier to agglomerate, the environmental protection and operation problems brought by the distillation of existing technologies were solved, and the aggregation temperature was reduced, and the preparation of high -performance carbon fiber was achieved.

CN119372811APending Publication Date: 2025-01-28山东开泰石化集团股份有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411798961.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-28
Patent Text Reader

Abstract

The invention discloses a method for preparing carbon fibers from acrylonitrile and ice crystal grade acrylic acid, and belongs to the technical field of carbon fiber preparation. The method comprises the following main production steps: 1) preparing ice crystal grade acrylic acid from industrial grade acrylic acid, 2) mixing two monomers according to a certain ratio, and carrying out water phase precipitation polymerization under a certain oxidation-reduction initiation system, 3) centrifuging, washing and drying powder, 4) crushing the powder, and 5) dissolving the powder to prepare a spinning solution. According to the invention, acrylonitrile and ice crystal grade acrylic acid are taken as monomers, and high-performance powder for dry spinning of carbon fiber precursors is prepared at a low temperature of 45-50 DEG C through a water phase precipitation polymerization method. The prepared precursor monofilament is high in strength, high in modulus and high in crystallinity, heat release in the carbonization process is smooth and stable and concentrated in the range of 230-260 DEG C, and heat dissipation in the carbonization process is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber preparation, and in particular relates to a method for preparing carbon fiber by utilizing acrylonitrile and ice-grade acrylic acid. Background Art

[0002] The application of ice-grade acrylic acid can effectively reduce the polymerization reaction temperature, reduce the influence of inhibitors, dimers, and impurities, and improve the structural regularity and crystallinity of the polymer powder. Carboxylic acid comonomers can reduce the activation energy of cyclopolymers, shift the cyclization starting temperature to low temperature, broaden the DSC exothermic peak, and make the pre-oxidation process smooth and controllable. At present, the preparation of high-performance carbon fiber powder requires the refinement of each monomer, which is basically achieved by distilling each monomer involved in the polymerization. Distillation increases the risk of self-polymerization of inert monomers and introduces other impurities. Environmental problems caused by the volatilization of monomers during the refining process also need to be solved.

[0003] In the prior art, patent CN103880649A describes a method for preparing high-yield ice crystal grade acrylic acid. The method can be operated in two stages through crystallization, sweating, and melting steps. First, the product is obtained by freezing, with a ratio of 60% to 70%. The remaining residual liquid is treated by chemical methods to convert impurities into high-boiling point substances, which enter the esterification stage as raw materials to remove high-boiling point substances in the production process of butyl acrylate. Although this method reduces costs to a certain extent and reduces the problem of difficult treatment of low-concentration residual acid, it still relies on chemical treatment and distillation steps, and fails to completely solve the environmental protection and operation problems in the distillation process. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a simple, easy-to-operate and high-yield method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing carbon fiber powder by using acrylonitrile and ice-grade acrylic acid, characterized in that the preparation steps are: 1) Add acrylonitrile and ice crystal grade acrylic acid into a 1# monomer kettle and stir evenly, wherein the proportion of acrylonitrile is 96.5wt%~99wt% and the proportion of ice crystal grade acrylic acid is 1wt%~3.5wt%; the ice crystal grade acrylic acid is prepared from industrial grade acrylic acid by freezing crystallization; 2) Add 0.7wt%~1.2wt% of the total monomer amount of the oxidation-reduction system initiator into the 2# monomer kettle, the molar ratio of the oxidant to the reductant in the oxidation-reduction system initiator is 1:1.5~2.5, and add water while stirring to prepare an initiator solution with a concentration of 0.4wt%~0.6wt% based on the oxidant amount; 3) Add water to the 3# monomer kettle; pre-add water to the reactor and heat it to 70℃~80℃, then start and maintain stirring; 4) Discharge each monomer kettle into the reactor, and control the discharge rate of each monomer kettle so that the total monomer content in the reactor is maintained at 17%~23%; after the reaction in the reactor is stable and exothermic, cool the material to 45℃~50℃ for polymerization reaction; 5) Adding sodium hydroxide solution of 0.05wt%~0.1wt% of the total amount of monomers to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction; the reaction slurry flows from the overflow port at the top of the reactor to the termination kettle which has been cooled to 7°C~13°C; the slurry in the termination kettle is repeatedly centrifuged and washed with water until the acrylonitrile monomer content in the filtrate is ≤50ppm; 6) Collect the washed powder, dry it to a water content of <0.5%, crush it and pass it through a 300-mesh sieve, dissolve the sieved powder in DMAC, swell and dissolve it at room temperature, and prepare a spinning solution with a solid content of 25% to 30%; 7) The spinning solution is spun through a dry single-channel spinning process to prepare primary fibers, and the primary fibers are washed, stretched, oiled, and heat-set to prepare carbon fiber precursors; the carbon fiber precursors are then oxidized and carbonized to obtain carbon fibers.

[0006] This patent uses ice crystal grade acrylic acid to participate in polymerization. Ice crystal grade acrylic acid has low content of inhibitors, dimers and impurities, and is simple to operate and easy to implement, which reduces production costs. Ice crystal grade acrylic acid is made from industrial grade acrylic acid by freezing and crystallization, without distillation, which overcomes the environmental protection and operation problems brought about by the distillation process in the prior art. After using ice crystal grade acrylic acid to participate in the polymerization, the polymerization temperature drops from 60°C to 45°C~50°C, and the polymer is white in color, low in branching, high in crystallinity and good in regularity; carboxylic acid comonomers can reduce the activation energy of cyclopolymers, transfer the starting temperature of cyclization to low temperature, broaden the DSC exothermic peak, reduce the temperature of the pre-oxidation process, and smoothly controllable. After spinning and carbonization, high-performance dry-process carbon fiber is prepared. The ice crystal grade acrylic acid obtained by the freezing crystallization method has a low content of inhibitors, dimers and impurities, which helps to improve the structural regularity and crystallinity of the final carbon fiber powder, thereby improving the performance of the carbon fiber.

[0007] Specifically, the freeze crystallization is to cool the industrial grade acrylic acid to -10℃~-5℃ so that the acrylic acid component therein is frozen into a solid state, and the impurities that are still in liquid state are recovered; the frozen solid acrylic acid is heated to 18℃~20℃ to melt, and the melted acrylic acid is then subjected to the above freezing and melting process to prepare ice crystal grade acrylic acid. By repeating the freeze crystallization process, high-purity ice crystal grade acrylic acid is effectively separated from the industrial grade acrylic acid. The obtained ice crystal acrylic acid has high purity and meets the purity requirements of this process. The inhibitor content in the obtained ice crystal grade acrylic acid is less than 1ppm, and the dimer content is less than 0.2ppm.

[0008] Preferably, in the above method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, the oxidation-reduction system initiator described in step 2) is an ammonium persulfate-sodium bisulfite initiator. The oxidation-reduction initiation system composed of ammonium persulfate-sodium bisulfite can reduce the activation energy of the free radical generation reaction and increase the polymerization reaction rate at a lower reaction temperature.

[0009] Preferably, in the above method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, the discharge rate of each monomer kettle is controlled in step 4) so ​​that the total monomer content in the reactor is maintained at 19% to 21%. By accurately controlling the total monomer content, the polymerization reaction is ensured to be carried out under optimal conditions, thereby improving the reaction efficiency and product quality.

[0010] Preferably, in the above method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, the reaction slurry in step 5) flows from the overflow port at the top of the reactor to a termination reactor that has been cooled to 9° C. to 10° C. Terminating the polymerization reaction at a lower temperature helps to reduce the degree of branching of the polymer, improve the crystallinity and regularity of the polymer, and ensure the performance of the final carbon fiber.

[0011] Preferably, in the above method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, the solid content of the spinning solution prepared in step 6) is 28% to 30%. The preferred solid content is more helpful to optimize the mechanical properties and surface characteristics of the obtained fiber.

[0012] Preferably, in the above method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, the fineness of the carbon fiber precursor obtained in step 7) is 1.6 dtex to 2.2 dtex. The obtained low-fineness precursor has a larger surface area per unit volume, which is conducive to the uniform oxidation reaction, thereby obtaining a more uniform carbon fiber.

[0013] Preferably, in the above method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, the tensile strength of the carbon fiber precursor obtained in step 7) is 5.6 cN / dtex~7.2 cN / dtex, and the modulus is 85 cN / dtex~102 cN / dtex.

[0014] Compared with the prior art, the method for preparing carbon fiber using acrylonitrile and ice crystal grade acrylic acid of the present invention has the following beneficial effects: the present invention discloses a method for preparing high-performance powder for dry spinning carbon fiber precursor by using acrylonitrile and ice crystal grade acrylic acid as monomers through an aqueous phase precipitation polymerization method at a relatively low temperature (45°C to 50°C) to reduce production costs. Ice crystal grade acrylic acid is prepared from industrial grade acrylic acid by freezing crystallization without distillation, thus overcoming the environmental protection and operation problems caused by the distillation process in the prior art. The invention discloses a method for preparing dry-process carbon fiber precursor. The method adopts ice crystal grade acrylic acid as a second monomer and prepares a high-performance polymer at a relatively low temperature. The dry-process carbon fiber precursor prepared by the polymer can be used to prepare high-performance polyacrylonitrile-based dry-process carbon fiber through carbonization. The prepared dry-process carbon fiber precursor can be used to prepare T700-grade carbon fiber with stable molecular weight (viscosity average, number average) and a molecular weight distribution width of less than 2.3%. The precursor single yarn prepared by the method has high strength, high modulus, high orientation degree and crystallinity. The heat release in the carbonization process is gentle and stable and concentrated in the range of 230°C to 260°C, which is conducive to heat dissipation in the carbonization process. DETAILED DESCRIPTION

[0015] The present invention is further described below in conjunction with specific embodiments, wherein Embodiment 1 is the best embodiment.

[0016] Example 1 1) Preparation of ice crystal grade acrylic acid, using physical freezing method, equipment shell and tube heat exchanger, industrial acrylic acid in the tube side, 45% methanol aqueous solution in the shell side. Methanol aqueous solution is cooled to -5℃ by ice maker, and heat exchanged with industrial acrylic acid in the tube side for cooling and freezing. Acrylic acid is cooled and frozen in the tubes, and impurities are recovered. The shell side is switched to methanol aqueous solution heated to 18℃ by electricity, the acrylic acid in the tubes is melted, and the above freezing process is repeated for the melted acrylic acid. The acrylic acid collected again is thawed, which is ice crystal grade acrylic acid. Ice crystal grade acrylic acid is prepared, with inhibitor content of 0.2ppm and dimer content of 0.05ppm, which is the monomer of polymerization reaction.

[0017] 2) Add acrylonitrile and ice-grade acrylic acid into the 1# monomer kettle according to the weight ratio, stir evenly at a speed of 120r / min, and the proportion of acrylonitrile is 98%, and the proportion of acrylic acid is 2%.

[0018] 3) Use ammonium persulfate-sodium bisulfite initiator at a ratio of 1:2 and 1% monomer ratio, add it into the 2# kettle, add high-purity water, and prepare it to a concentration of 0.5% (calculated by the mass of the oxidant), and stir evenly at a speed of 100r / min.

[0019] 4) Add high-purity water with a pH of 7.5 into the 3# monomer kettle.

[0020] 5) Add 70% of the volume of high-purity water into the reactor, heat the high-purity water in the reactor to 75°C, and stir at a speed of 160r / min.

[0021] 6) Open the feed of each monomer reactor to maintain the monomer ratio in the reactor at 20%.

[0022] 7) After the reaction is stable and exothermic, use chilled water in the reactor jacket to cool the temperature of the materials in the reactor to 47°C.

[0023] 8) Add 0.07 wt% sodium hydroxide solution to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction.

[0024] 9) The reaction slurry flows from the overflow port at the top of the reactor to the termination reactor which has been cooled to 10°C.

[0025] 10) The slurry in the reactor was passed through a centrifuge, centrifuged and washed with water, and the process was repeated three times. The acrylonitrile monomer content in the filtrate was 24 ppm.

[0026] 11) Collect the powder after washing, dry it in a vacuum oven with a vacuum degree of less than 0.8 MPa at 65°C until the water content of the polymer is less than 0.5%, crush it, dry it again, and sieve it (300 mesh).

[0027] 12) Collect the crushed and sieved powder, dissolve it in DMAC, swell it at room temperature (about 25°C) and then dissolve it to prepare a spinning solution with a solid content of 28%.

[0028] 13) The spinning solution is spun through a dry single-channel spinning process to produce primary fibers.

[0029] 14) The primary fibers are further washed, drawn, oiled, and heat-set to produce carbon fiber precursors with a fineness of 1.8 dtex, a tensile strength of 7.2 cN / dtex, and a modulus of 102 cN / dtex.

[0030] 15) Pre-oxidation and carbonization of carbon fiber precursor to prepare carbon fiber.

[0031] 16) Test the tensile strength of carbon fiber: 4012MPa, tensile modulus: 363MPa.

[0032] Example 2 1) Preparation of ice crystal grade acrylic acid, using physical freezing method, equipment shell and tube heat exchanger, industrial acrylic acid in the tube side, 42% methanol aqueous solution in the shell side. The methanol aqueous solution is cooled to -8°C by ice making machine, and heat exchanged with industrial grade acrylic acid in the tube side for cooling and freezing. The acrylic acid is frozen in the tube after cooling, and impurities are recovered. The shell side is switched to methanol aqueous solution heated to 19°C by electricity, the acrylic acid in the tube is melted, and the above freezing process is repeated for the melted acrylic acid. The acrylic acid collected again is thawed, which is ice crystal grade acrylic acid. Ice crystal grade acrylic acid is prepared, with inhibitor content of 0.6ppm and dimer content of 0.08ppm, which is the monomer of polymerization reaction.

[0033] 2) Add acrylonitrile and ice-grade acrylic acid into the 1# monomer kettle according to the weight ratio, stir evenly at a speed of 120r / min, and the proportion of acrylonitrile is 98%, and the proportion of acrylic acid is 2%.

[0034] 3) Use ammonium persulfate-sodium bisulfite initiator at a ratio of 1:2 and a monomer ratio of 0.9%, add it into the 2# kettle, add high-purity water, prepare a concentration of 0.5% (calculated by the mass of the oxidant), and stir evenly at a speed of 100r / min.

[0035] 4) Add high-purity water with a pH of 7.5 into the 3# monomer kettle.

[0036] 5) Add 65% of the volume of high-purity water into the reactor, heat the high-purity water in the reactor to 75°C, and stir at a speed of 160 r / min.

[0037] 6) Open each monomer kettle and feed in a certain proportion to maintain the monomer ratio in the reactor at 19%.

[0038] 7) After the reaction is stable and exothermic, use chilled water in the reactor jacket to cool the material in the reactor to 48°C.

[0039] 8) Add 0.09 wt% sodium hydroxide solution to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction.

[0040] 9) The reaction slurry flows from the overflow port at the top of the reactor into the termination reactor which has been cooled to 9°C.

[0041] 10) The slurry in the terminating kettle is passed through a centrifuge for centrifugation and water washing, which is repeated 4 times until the acrylonitrile monomer content in the filtrate reaches 20 ppm.

[0042] 11) Collect the powder after washing, dry it in a vacuum oven with a vacuum degree of less than 0.8 MPa at 65°C until the water content of the polymer is less than 0.5%, crush it, dry it again, and sieve it (300 mesh).

[0043] 12) Collect the crushed and sieved powder, dissolve it in DMAC, swell it at room temperature (about 25°C) and then dissolve it to prepare a spinning solution with a solid content of 29%.

[0044] 13) The spinning solution is spun through a dry single-channel spinning process to produce primary fibers.

[0045] 14) The spun fibers are further washed, drawn, oiled, and heat-set to produce carbon fiber precursors with a fineness of 2.0 dtex, a tensile strength of 7.2 cN / dtex, and a modulus of 96 cN / dtex.

[0046] 15) Pre-oxidation and carbonization of carbon fiber precursor to prepare carbon fiber.

[0047] 16) Test the tensile strength of carbon fiber: 3927MPa, tensile modulus: 358MPa.

[0048] Example 3 1) Preparation of ice crystal grade acrylic acid, using physical freezing method, equipment shell and tube heat exchanger, industrial acrylic acid in the tube side, 44% methanol aqueous solution in the shell side. The methanol aqueous solution is cooled to -6°C by ice making machine, and heat exchanged with industrial grade acrylic acid in the tube side for cooling and freezing. The acrylic acid is frozen in the tube after cooling, and impurities are recovered. The shell side is switched to methanol aqueous solution heated to 19°C by electricity, the acrylic acid in the tube is melted, and the above freezing process is repeated for the melted acrylic acid. The acrylic acid collected again is thawed, which is ice crystal grade acrylic acid. Ice crystal grade acrylic acid is prepared, with inhibitor content of 0.4ppm and dimer content of 0.1ppm, which is the monomer of polymerization reaction.

[0049] 2) Add acrylonitrile and ice-grade acrylic acid into the 1# monomer kettle according to the weight ratio, stir evenly at a speed of 120r / min, and the proportion of acrylonitrile is 97% and acrylic acid is 3%.

[0050] 3) Use ammonium persulfate-sodium bisulfite initiator at a ratio of 1:2 and a monomer ratio of 1.1%, add it into the 2# kettle, add high-purity water, prepare a concentration of 0.6% (calculated by the mass of the oxidant), and stir evenly at a speed of 100r / min.

[0051] 4) Add high-purity water with a pH of 7.5 into the 3# monomer kettle.

[0052] 5) Add 75% of the volume of high-purity water into the reactor, heat the high-purity water in the reactor to 78°C, and stir at a speed of 160r / min.

[0053] 6) Open each monomer kettle and feed in a certain proportion to maintain the monomer ratio in the reactor at 21%.

[0054] 7) After the reaction is stable and exothermic, use chilled water in the reactor jacket to cool the material in the reactor to 49°C.

[0055] 8) Add 0.07 wt% sodium hydroxide solution to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction.

[0056] 9) The reaction slurry flows from the overflow port at the top of the reactor to the termination reactor which has been cooled to 10°C.

[0057] 10) The slurry in the terminating kettle is passed through a centrifuge for centrifugation and water washing, which is repeated twice until the acrylonitrile monomer content in the filtrate reaches 40 ppm.

[0058] 11) Collect the powder after washing, dry it in a vacuum oven with a vacuum degree of less than 0.8 MPa at 65°C until the water content of the polymer is less than 0.5%, crush it, dry it again, and sieve it (300 mesh).

[0059] 12) Collect the crushed and sieved powder, dissolve it in DMAC, swell it at room temperature (about 25°C) and then dissolve it to prepare a spinning solution with a solid content of 30%.

[0060] 13) The spinning solution is spun through a dry single-channel spinning process to produce primary fibers.

[0061] 14) The primary fibers are further washed, drawn, oiled, and heat-set to produce carbon fiber precursors with a fineness of 2.0 dtex, a tensile strength of 6.6 cN / dtex, and a modulus of 95 cN / dtex.

[0062] 15) Pre-oxidation and carbonization of carbon fiber precursor to prepare carbon fiber.

[0063] 16) Test the tensile strength of carbon fiber: 3894MPa, tensile modulus: 328MPa.

[0064] Example 4 1) Preparation of ice crystal grade acrylic acid adopts physical freezing method, with shell-and-tube heat exchanger, industrial acrylic acid in the tube side, and 40% methanol aqueous solution in the shell side. The methanol aqueous solution is cooled to -5°C by ice maker, and heat exchanged with industrial acrylic acid in the tube side for cooling and freezing. The acrylic acid is frozen in the tubes after cooling, and impurities are recovered. The shell side is switched to methanol aqueous solution heated to 18°C ​​by electricity, the acrylic acid in the tubes is melted, and the above freezing process is repeated for the melted acrylic acid. The acrylic acid collected again is thawed to obtain ice crystal grade acrylic acid. Ice crystal grade acrylic acid is prepared with inhibitor content of 0.6ppm and dimer content of 0.08ppm, which is the monomer for polymerization reaction.

[0065] 2) Add acrylonitrile and ice-grade acrylic acid into the 1# monomer kettle according to the weight ratio, stir evenly at a speed of 120r / min, and the proportion of acrylonitrile is 99% and acrylic acid is 1%.

[0066] 3) Use ammonium persulfate-sodium bisulfite initiator at a ratio of 1:1.5 and a monomer ratio of 1.2%, add it into the 2# kettle, add high-purity water, prepare a concentration range of 0.6% (calculated by the mass of the oxidant), and stir evenly at a speed of 100r / min.

[0067] 4) Add high-purity water with a pH of 8 into the 3# monomer kettle.

[0068] 5) Add 90% of the volume of high-purity water into the reactor, heat the high-purity water in the reactor to 70°C, and stir at a speed of 160r / min.

[0069] 6) Open each monomer kettle and feed in a certain proportion to maintain the monomer ratio in the reactor at 17%.

[0070] 7) After the reaction is stable and exothermic, use chilled water in the reactor jacket to cool the temperature of the materials in the reactor to 50°C.

[0071] 8) Add 0.1 wt% sodium hydroxide solution to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction.

[0072] 9) The reaction slurry flows from the overflow port at the top of the reactor into the termination reactor which has been cooled to 7°C.

[0073] 10) The slurry in the reactor was passed through a centrifuge for centrifugation and water washing, which was repeated three times until the acrylonitrile monomer content in the filtrate reached 38 ppm.

[0074] 11) Collect the powder after washing, dry it in a vacuum oven with a vacuum degree of less than 0.8 MPa at 65°C until the water content of the polymer is less than 0.5%, crush it, dry it again, and sieve it (300 mesh).

[0075] 12) Collect the crushed and sieved powder, dissolve it in DMAC, swell it at room temperature (about 25°C) and then dissolve it to prepare a spinning solution with a solid content of 26%.

[0076] 13) The spinning solution is spun through a dry single-channel spinning process to produce primary fibers.

[0077] 14) The primary fibers are further washed, drawn, oiled, and heat-set to produce carbon fiber precursors with a fineness of 1.6 dtex, a tensile strength of 5.6 cN / dtex, and a modulus of 85 cN / dtex.

[0078] 15) Pre-oxidation and carbonization of carbon fiber precursor to prepare carbon fiber.

[0079] 16) Test the tensile strength of carbon fiber: 3725MPa, tensile modulus: 314MPa.

[0080] Example 5 1) Preparation of ice crystal grade acrylic acid, using physical freezing method, equipment shell and tube heat exchanger, industrial acrylic acid in the tube side, 45% methanol aqueous solution in the shell side. Methanol aqueous solution is cooled to -10℃ by ice machine, and heat exchanged with industrial grade acrylic acid in the tube side for cooling and freezing. Acrylic acid is frozen in the tube after cooling, and impurities are recovered. The shell side is switched to methanol aqueous solution heated to 20℃ by electricity, the acrylic acid in the tube is melted, and the above freezing process is repeated for the melted acrylic acid. The acrylic acid collected again is thawed, which is ice crystal grade acrylic acid. Ice crystal grade acrylic acid is prepared, with inhibitor content of 0.7ppm and dimer content of 0.1ppm, which is the monomer of polymerization reaction.

[0081] 2) Add acrylonitrile and ice-grade acrylic acid into the 1# monomer kettle according to the weight ratio, stir evenly at a speed of 120r / min, and the proportion of acrylonitrile is 96.5%, and acrylic acid: 3.5%.

[0082] 3) Use ammonium persulfate-sodium bisulfite initiator at a ratio of 1:2.5 and a monomer ratio of 1.2%, add it into the 2# kettle, add high-purity water, prepare a concentration range of 0.4% (calculated by the mass of the oxidant), and stir evenly at a speed of 100r / min.

[0083] 4) Add high-purity water with a pH of 7 into the 3# monomer kettle.

[0084] 5) Add 60% of the volume of high-purity water into the reactor, heat the high-purity water in the reactor to 80°C, and stir at a speed of 160r / min.

[0085] 6) Open each monomer kettle and feed in a certain proportion to maintain the monomer ratio in the reactor at 23%.

[0086] 7) After the reaction is stable and exothermic, use chilled water in the reactor jacket to cool the material in the reactor to 45°C.

[0087] 8) Add 0.05 wt% sodium hydroxide solution to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction.

[0088] 9) The reaction slurry flows from the overflow port at the top of the reactor into the termination reactor which has been cooled to 13°C.

[0089] 10) The slurry in the reactor was passed through a centrifuge for centrifugation and water washing, which was repeated three times until the acrylonitrile monomer content in the filtrate reached 33 ppm.

[0090] 11) Collect the powder after washing, dry it in a vacuum oven with a vacuum degree of less than 0.8 MPa at 65°C until the water content of the polymer is less than 0.5%, crush it, dry it again, and sieve it (300 mesh).

[0091] 12) Collect the crushed and sieved powder, dissolve it in DMAC, swell it at room temperature (about 25°C) and then dissolve it to prepare a spinning solution with a solid content of 25%.

[0092] 13) The spinning solution is spun through a dry single-channel spinning process to produce primary fibers.

[0093] 14) The primary fibers are further washed, drawn, oiled, and heat-set to produce carbon fiber precursors with a fineness in the range of 2.2 dtex, a tensile strength of 5.9 cN / dtex, and a modulus of 88 cN / dtex.

[0094] 15) Pre-oxidation and carbonization of carbon fiber precursor to prepare carbon fiber.

[0095] 16) Test carbon fiber tensile strength: 3742MPa, tensile modulus: 302MPa.

[0096] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid, characterized in that: The preparation steps are: 1) Add acrylonitrile and ice crystal grade acrylic acid into a 1# monomer kettle and stir evenly, wherein the proportion of acrylonitrile is 96.5wt%~99wt% and the proportion of ice crystal grade acrylic acid is 1wt%~3.5wt%; the ice crystal grade acrylic acid is prepared from industrial grade acrylic acid by freezing crystallization; 2) Add 0.7wt%~1.2wt% of the total monomer amount of the oxidation-reduction system initiator into the 2# monomer kettle, the molar ratio of the oxidant to the reductant in the oxidation-reduction system initiator is 1:1.5~2.5, and add water while stirring to prepare an initiator solution with a concentration of 0.4wt%~0.6wt% based on the oxidant amount; 3) Add water into the 3# monomer kettle; Add water into the reactor and heat it to 70℃~80℃, then start stirring. 4) Discharge each monomer kettle into the reactor, and control the discharge rate of each monomer kettle so that the total monomer content in the reactor is maintained at 17%~23%; after the reaction in the reactor is stable and exothermic, cool the material to 45℃~50℃ for polymerization reaction; 5) Adding sodium hydroxide solution of 0.05wt%~0.1wt% of the total amount of monomers to the overflow port of the reactor to adjust the pH value of the slurry and terminate the polymerization reaction; the reaction slurry flows from the overflow port at the top of the reactor to the termination kettle which has been cooled to 7°C~13°C; the slurry in the termination kettle is repeatedly centrifuged and washed with water until the acrylonitrile monomer content in the filtrate is ≤50ppm; 6) Collect the washed powder, dry it to a water content of <0.5%, crush it and pass it through a 300-mesh sieve, dissolve the sieved powder in DMAC, swell and dissolve it at room temperature, and prepare a spinning solution with a solid content of 25% to 30%; 7) The spinning solution is spun through a dry single-channel spinning process to prepare primary fibers, and the primary fibers are washed, drawn, oiled, and heat-set to prepare carbon fiber precursors; the carbon fiber precursors are then oxidized and carbonized to obtain carbon fiber powder.

2. The method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: The frozen crystallization is to cool industrial-grade acrylic acid to -10°C to -5°C to freeze the acrylic acid component therein into a solid state, and recover the impurities that are still in liquid state; heat the frozen solid acrylic acid to 18°C ​​to 20°C to melt it, and then repeat the above freezing and melting process of the melted acrylic acid to prepare ice crystal grade acrylic acid.

3. A method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid according to claim 1 or 2, characterized in that: The content of polymerization inhibitor in the ice crystal grade acrylic acid is less than 1ppm, and the content of dimer is less than 0.2ppm.

4. The method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: The oxidation-reduction system initiator described in step 2) is ammonium persulfate-sodium bisulfite initiator.

5. The method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: In step 4), the discharge rate of each monomer kettle is controlled so that the total monomer content in the reactor is maintained at 19% to 21%.

6. The method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: In step 5), the reaction slurry flows from the overflow port at the top of the reactor into the termination reactor which has been cooled to 9°C-10°C.

7. The method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: The solid content of the spinning solution prepared in step 6) is 28% to 30%.

8. The method for preparing carbon fiber by using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: The fineness of the carbon fiber precursor obtained in step 7) is between 1.6 dtex and 2.2 dtex.

9. The method for preparing carbon fiber using acrylonitrile and ice-grade acrylic acid according to claim 1, characterized in that: The tensile strength of the carbon fiber precursor obtained in step 7) is 5.6 cN / dtex~7.2 cN / dtex, and the modulus is 85 cN / dtex~102 cN / dtex.

Citation Information

Patent Citations

  • Method for preparing high-yield ice crystal grade acrylic acid

    CN103880649A